2014
DOI: 10.1097/aog.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hypertension, Medication Use, and Hypospadias in the National Birth Defects Prevention Study

Abstract: OBJECTIVE To investigate whether antihypertensive classes and specific medications in early pregnancy increase the risk of severe hypospadias and to assess prior associations detected for late-treated and untreated hypertension in the National Birth Defects Prevention Study. METHODS Using telephone interviews from mothers of 2,131 children with severe hypospadias and 5,129 nonmalformed male control children for 1997–2009 births in a population-based case–control study, we estimated adjusted odds ratios (ORs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 35 publications
1
35
1
Order By: Relevance
“…There were five other reports (published between 2008 and 2014) where investigators found an association between hypospadias and preeclampsia also in growth restricted fetuses [2024]. The common theme as to the pathophysiology of hypospadias in infants delivered of women with preeclampsia was placental insufficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were five other reports (published between 2008 and 2014) where investigators found an association between hypospadias and preeclampsia also in growth restricted fetuses [2024]. The common theme as to the pathophysiology of hypospadias in infants delivered of women with preeclampsia was placental insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The common theme as to the pathophysiology of hypospadias in infants delivered of women with preeclampsia was placental insufficiency. How placental insufficiency might interfere with closure of the urethra was unclear [2024]. …”
Section: Discussionmentioning
confidence: 99%
“…Infants born to mothers with reported maternal diseases, such as gestational diabetes mellitus (13,14), hypertension (15), and thyroid disorders (16,17), or adverse environmental exposure (18)(19)(20)(21)(22) during pregnancy, were excluded from this analysis because of the possible association of these factors with birth defects. The final data, involving 2,060 live-born infants, delivered after IVF with ICSI and FET, were stratified into groups according to the method of ovarian stimulation: 587 births after LPS, 1,257 births after the standard GnRH-a short protocol, and 216 births after mild ovarian stimulation.…”
Section: Study Population and Designmentioning
confidence: 99%
“…21 These include congenital heart disease, esophageal atresia, and hypospadias. [21][22][23] In a systematic review and metaanalysis, Ramakrishnan and colleagues 21 found that congenital anomalies were more common in both treated and untreated hypertension, although the risk was greater in treated hypertension. Van Zutphen and colleagues 23 demonstrated a higher incidence of hypospadias in untreated hypertension and hypertension treated with nonselective b-blockers, specifically labetalol and propranolol.…”
Section: Pharmacologic Treatment Optionsmentioning
confidence: 98%
“…In these women, delivery can be delayed for 48 hours for administration of corticosteroids for fetal lung maturity in the absence of uncontrollable severe hypertension, eclampsia, pulmonary edema, placental abruption, disseminated intravascular coagulation, or nonreassuring fetal status. The management of preeclampsia with severe features before viability (23)(24) weeks in most centers) should involve consultation with a specialist in maternalfetal medicine.…”
Section: Delivery Planningmentioning
confidence: 99%